Strategies To Improve Financial Performance With A Signaling Theory Perspective - Adelia Adelia; Khairudin Khairudin; Aminah Aminah (International Journal of Economics, Business and Innovation Research, 2024)
Financial performance is the financial condition of an entity at a certain time, which is determined by analysing the financial statements, to determine whether the company is good or bad. The aim of this study is to determine whether profitability and liquidity affect the financial performance controlled by the size of the company in all wireless-telecommunications-subsector-companies listed on the Indonesian Stock Exchange in 2019-2022. The study is a quantitative study, with a total of 56 samples determined by companies using purposive sampling methods for sample-taking. Data processing techniques are based on several linear regression analysis tests with SPSS as an Analysis Tool. The results show that (1) profitability has a significant positive impact on financial performance, and (2) liquidity has a positive and significant impact on its financial performance. The lack of research samples and the low ability of independent variables to influence dependent variables, which is only 32 %, are the limitations of this research. Therefore, it is recommended for further researchers to increase the sample of research and other independent variables such as (1) solvency and (2) capital structure, (3) leverage and (4) debt film, which explains its impact on financial performance.